CONTESTED HEGEMONY: RUSSIA’S APPROACH TO THE MILITARY AND ECONOMIC PREDOMINANCE OF THE US IN WORLD AFFAIRSHEGEMONIA CONTESTADA: A ABORDAGEM RUSSA QUANTO À PREDOMINÂNCIA MILITAR E ECONÔMICA GLOBAL DOS EUA - Bezerra, Valdir da Silva (Caderno de Relações Internacionais, 2020)
This paper discusses the Russian approach, from a rhetorical and practical viewpoint, regarding the military and economic predominance of the United States in the International System. The research method adopted was based on the compilation of statements by Russian authorities about the US position on the global stage, as well as on the presentation of the main initiatives and actions taken by the Kremlin, particularly from the 2000s onwards, in opposition to US interests both in the military and economic spheres. The first section initially deals with Russia’s intervention in Syria and Moscow's actions vis-a-vis the dismantling of bilateral nuclear-force treaties signed between the US and the Soviet Union during the Cold War. The second section brings the Russian articulation within the BRICS group as a criticism to American (and Western) privileges within institutions such as the IMF and the World Bank, posteriorly pointing out to the steps taken by Moscow in its quest to make the Russian economy less dependent on the dollar. We conclude by observing that in both military and economic aspects Moscow has obtained moderate results in view of its aspirations regarding the role of counterweight to the American power in International Relations.